2006
DOI: 10.1152/jn.00793.2005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Modulates Taste Responsiveness and Stimulates Gustatory Neurons in the Rat Geniculate Ganglion

Abstract: In humans, temperature influences taste intensity and quality perception, and thermal stimulation itself may elicit taste sensations. However, peripheral coding mechanisms of taste have generally been examined independently of the influence of temperature. In anesthetized rats, we characterized the single-cell responses of geniculate ganglion neurons to 0.5 M sucrose, 0.1 M NaCl, 0.01 M citric acid, and 0.02 M quinine hydrochloride at a steady, baseline temperature (adapted) of 10, 25, and 40 degrees C; gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
77
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 46 publications
19
77
2
Order By: Relevance
“…Most electrophysiological investigations in the taste field are employed at room temperature. In rats, the majority taste stimuli are severely reduced if not abolished below room temperature (Breza et al 2006). Additionally, we (Breza et al 2006;Lu et al 2012) and Lyall et al (2004) have shown that responses to some taste stimuli increase with increasing temperature, whereas responses to other taste stimuli show an inverted U-shaped function.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Most electrophysiological investigations in the taste field are employed at room temperature. In rats, the majority taste stimuli are severely reduced if not abolished below room temperature (Breza et al 2006). Additionally, we (Breza et al 2006;Lu et al 2012) and Lyall et al (2004) have shown that responses to some taste stimuli increase with increasing temperature, whereas responses to other taste stimuli show an inverted U-shaped function.…”
mentioning
confidence: 82%
“…In rats, the majority taste stimuli are severely reduced if not abolished below room temperature (Breza et al 2006). Additionally, we (Breza et al 2006;Lu et al 2012) and Lyall et al (2004) have shown that responses to some taste stimuli increase with increasing temperature, whereas responses to other taste stimuli show an inverted U-shaped function. However, much is still unknown on how temperature influences taste intensity within (e.g., sucrose vs. sucralose or HCl vs. acetic acid) and across separate taste qualities in the peripheral nervous system.…”
mentioning
confidence: 82%
See 3 more Smart Citations